Assessment of the structural stability of Blockhaus timber log-walls under in-plane compression via full-scale buckling experiments. (1st March 2015) - Bedon, C.; Rinaldin, G.; Izzi, M.; Fragiacomo, M.; Amadio, C.
Highlights: Full-scale buckling experiments are performed on in-plane compressed timber Blockhaus log-haus walls. Timber log-haus walls are characterized by high slenderness ratio and low modulus of elasticity. The effects of various geometrical aspects on their structural response are experimentally assessed. Simple analytical formulations are derived from classical theory of plate and column buckling. Abstract: Blockhaus structural systems are obtained by assembling multiple timber logs able to interact with each other by means of simple mechanisms (e.g. contacts, tongues and grooves, and carpentry joints, also referred to as 'corner' joints). Although these systems have ancient origins, the structural behaviour of Blockhaus systems under well-defined loading and boundary conditions is still complex to predict. The paper focuses on the assessment of the typical buckling behaviour and resistance of in-plane compressed timber log-walls. The effects of various mechanical and geometrical aspects such as in-plane rigid inter-storey floors, load eccentricities, different types of lateral restraints, openings (e.g. doors or windows) or additional metal stiffeners, are investigated by means of full-scale buckling experiments. Results are then critically discussed and preliminarily assessed via analytical formulations taken from classical theory of plate buckling and column buckling. Although further advanced studies are required for the development of a generalized buckling design method, it is shown that several mechanical and geometrical aspects should be properly taken into account to correctly predict the structural capacity of Blockhaus systems under in-plane compression.